Effect of bone geometry on stress distribution patterns in the equine metacarpophalangeal joint - Easton, Katrina L., author; Kawcak, Chris, advisor; McIlwraith, Wayne, committee member; Puttlitz, Christian, committee member; James, Susan, committee member; Shelburne, Kevin, committee member; Heyliger, Paul, committee member (Colorado State University. Libraries, 2012)
Catastrophic injury of the equine metacarpophalangeal joint is of major concern for both the equine practitioner and the American public. It is one of the major reasons for retirement and sometimes euthanasia of Thoroughbred racehorses. The most common type of catastrophic injury is fracture of the proximal sesamoid bones and lateral condyle of the third metacarpal bone. Many times these injuries are so disastrous that there is no possibility of fixing them. Even in the injuries that are able to be fixed, complications arising from the fracture such as support limb laminitis may ultimately lead to the demise of the horse. Therefore, prevention of these types of injuries is key. In order to decrease the incidence of injury, it is important to understand the risk factors and pathogenesis of disease that leads to them. This project was established to create a finite element model of the equine metacarpophalangeal joint in order to investigate possible risk factors, namely bone geometry, and its effect on the stress distribution pattern in the joint. The first part of the study involved in vitro experiments in order to provide a comprehensive dataset of ligament, tendon, and bone strain and pressure distribution in the joint with which to validate the finite element model. Eight forelimbs from eight different horses were tested on an MTS machine to a load equivalent to that found at the gallop. Beyond providing data for validation, the study was the first to the author's knowledge to measure surface contact pressure between the distal condyles of the third metacarpal bone and the proximal sesamoid bones. A pressure distribution pattern that could lead to an area of high tension in the area of the parasagittal groove was found. This result could help explain the high incidence of lateral condylar fractures that initiate in this location. The second part of this study focused on the development and validation of a finite element model of the metacarpophalangeal joint. A model was created based on computed tomography (CT) data. It included the third metacarpal bone, the proximal phalanx, the proximal sesamoid bones, the suspensory ligament, medial and lateral collateral ligaments, medial and lateral collateral sesamoidean ligaments, medial and lateral oblique sesamoidean ligaments, and the straight sesamoidean ligament. The mesh resolution was varied to create three models to allow for convergence. The converged model was then validated using data from the previous part of the study as well as data from the literature. The result was a finite element model containing 121,533 nodes, 112,633 hexahedral elements, and 10 non-linear springs. The final section of this study used the converged and validated finite element model to study the effect of varying bone geometry. The model was morphed based on CT data from three horses: control, lateral condylar fracture, and contralateral limb to lateral condylar fracture. There was an area similar between all three groups of increased stress in the palmar aspect of the parasagittal grooves where fractures are thought to initiate. Other results showed distinct differences in the stress distribution pattern between the three groups. Further investigation into these differences may help increase the understanding of a horse's predisposition to injury. In conclusion, this study has shown that joint geometry plays a role in the stress distribution patterns found in the equine metacarpophalangeal joint. The differences in these patterns between the three groups may help explain the increased risk of a catastrophic injury for some horses. Further studies are warranted to better define the parameters leading to these changes.
Keywords: catastrophic injury; metacarpophalangeal joint; finite element model; equine